Lack of ACTPK1, an STY kinase, enhances ammonium uptake and use, and promotes growth of rice seedlings under sufficient external ammonium. (17th February 2018) - Beier, Marcel P.; Obara, Mitsuhiro; Taniai, Akiko; Sawa, Yuki; Ishizawa, Jin; Yoshida, Haruki; Tomita, Narumi; Yamanaka, Tsuyoshi; Ishizuka, Yawara; Kudo, Syuko; Yoshinari, Akira; Takeuchi, Shiho; et al.
Summary: Ammonium influx into plant roots via the high‐affinity transport system (HATS) is down‐modulated under elevated external ammonium, preventing ammonium toxicity. In ammonium‐fed Arabidopsis, ammonium transporter 1 (AMT1) trimers responsible for HATS activity are allosterically inactivated in a dose‐dependent manner via phosphorylation of the conserved threonine at the carboxyl‐tail by the calcineurin B‐like protein 1‐calcineurin B‐like protein‐interacting protein kinase 23 complex and other yet unidentified protein kinases. Using transcriptome and reverse genetics in ammonium‐preferring rice, we revealed the role of the serine/threonine/tyrosine protein kinase gene OsACTPK1 in down‐modulation of HATS under sufficient ammonium. In wild‐type roots, ACTPK1 mRNA and protein accumulated dose‐dependently under sufficient ammonium. To determine the function of ACTPK1, two independent mutants lacking ACTPK1 were produced by retrotransposon Tos17 insertion. Compared with segregants lacking insertions, the two mutants showed decreased root growth and increased shoot growth under 1 mm ammonium due to enhanced ammonium acquisition, via aberrantly high HATS activity, and use. Furthermore, introduction of OsACTPK1 cDNA fused to the synthetic green fluorescence protein under its own promoter complemented growth and the HATS influx, and suggested plasma membrane localization. Root cellular expression of OsACTPK1 also overlapped with that of ammonium‐induced OsAMT1;1 and OsAMT1;2 . Meanwhile, threonine‐phosphorylated AMT1 levels were substantially decreased in roots of ACTPK1‐deficient mutants grown under sufficient ammonium. Bimolecular fluorescence complementation assay further confirmed interaction between ACTPK1 and AMT1;2 at the cell plasma membrane. Overall, these findings suggest that ACTPK1 directly phosphorylates and inactivates AMT1;2 in rice seedling roots under sufficient ammonium. Significance Statement: High‐affinity ammonium transporter 1 (AMT1) proteins located in the plasma membrane in plant roots are inactivated via phosphorylation of the conserved threonine residue at the cytoplasmic carboxyl‐tail under elevated external ammonium, preventing ammonium toxicity. In this study, we identified the role of a serine/threonine/tyrosine protein kinase, ACTPK1, in phosphorylation and inactivation of ammonium‐induced AMT1;2 in ammonium‐preferring rice grown under sufficient ammonium.